Päivittäisen istumisen määrän yhteys vaihdevuosi-ikäisten naisten alaraajojen suorituskykyyn - Huovila, Pinja (2025)
Many people sit excessively from a health and well-being perspective. Physical performance declines with aging. Women’s performance, partly due to menopausal changes, declines faster than men’s. Identifying factors associated with physical performance is essential for prevention and health promotion. The aim of this master's thesis was to investigate whether the average daily sitting time is associated with lower-limb performance in menopausal women. Performance was assessed using the countermovement jump test and the knee extension strength test. The tests measure lower-limb explosive power and isometric muscle strength.